Factors Influencing Farmers’ Adoption of CRIN TC Cocoa Hybrid Technology in Oyo State, Nigeria - Jonathan Akinsola Akinwale; Oluwajoba Emmanuel Folarin (Indonesian Coffee and Cocoa Research Institute, 2018)
Cocoa production in Nigeria has been on a downward trend in recent years. Low productivity from ageing cocoa trees and low technology uptake among the farmers are some of the contributing factors. Efforts are therefore ongoing to introduce cocoa hybrid technology to enhance cocoa farmers’ productivity. This study therefore examines factors influencing adoption of CRIN TC (TC 1- 8) cocoa hybrid technology among cocoa farmers in Oyo state, Nigeria. Using multi-stage sampling procedure, 80 respondents were sampled for the study. A well-structured questionnaire was used to gather information from the farmers. Data was analysed using descriptive statistics and regression analysis. The results revealed that most (83.8%) of the farmers were male with the mean age of 55 years. It also showed that 43.8% of the farmers completed primary education while majority (51.3%) had a household size of 6-10 persons with a mean household size of 5 persons. The study also showed that 80% of the cocoa farmers got their information regarding cocoa hybrid through research institute. It was also found that most of the farmers had high level of adoption. Meanwhile, high cost of agrochemicals was identified as a major constraint toward adoption of CRIN TC (TC 1- 8) cocoa hybrid. Meanwhile, farmers age (β=-0.007) farming experience (β=-0.004) were identified as the factors influencing farmers’ adoption of the cocoa hybrid. Governments at various levels are encouraged to subsidise the price of agrochemicals which was discovered as major constraint to adoption of CRIN TC (TC1-TC8) cocoa hybrid technology.